Pengaruh Strategi Promosi Dan Harga Terhadap Keputusan Pembelian Yang Dimediasi Oleh Minat Beli Kain Sasirangan Bordir - Periyadi Periyadi; Junaidi Junaidi; Noorlaily Maulida (Islamic University of Kalimantan MAB Banjarmasin, 2020)
The main objective of this research is to examine and analyze how much promotion strategy and price influence purchasing decisions mediated by buying interest in embroidery sasirangan fabrics. The method used in this research is quantitative research with a formal research procedure design that contains clear definitions of research objectives and information needs. To answer and achieve the research objectives, regression analysis will be used. The object of this research is the consumer or potential consumer of the Sasirangan Embroidered cloth